Basal cell carcinomas on sun‐protected vs. sun‐exposed body sites: a comparison of phenotypic and environmental risk factors. Issue 4 (14th April 2015) - Khalesi, Mohammad; Whiteman, David C.; Rosendahl, Cliff; Johns, Richard; Hackett, Timothy; Cameron, Alan; Waterhouse, Mary; Lucas, Robyn M.; Kimlin, Michael G.; Neale, Rachel E.; the NHMRC Centre of Research Excellence in Sun and Health
Summary Background Basal cell carcinoma (BCC) is the most commonly diagnosed cancer in White populations. There are indications that risk factors for BCC may differ according to the anatomic site of the tumour but this is not well understood. Purpose To compare phenotypic and environmental risk factors for BCCs arising on sun‐protected sites with that of those on sun‐exposed sites. Methods We conducted a case–case study in which people who had been diagnosed with incident BCC were recruited between February 2012 and September 2013 in Brisbane, Australia. Results Fair skin (OR: 4.50; 95% CI: 1.22, 16.59), having more than 15 lesions frozen/burnt off compared to less than 5 (OR: 5.68; 95% CI: 1.78, 18.08) and severe acne (OR: 5.25; 95% CI: 1.34, 20.56) were associated with increased risk of BCC on sun‐protected sites. The presence of more than 5 nevi on the body was associated with decreased risk (OR: 0.28; 95% CI: 0.11, 0.71). Conclusions BCCs on sun‐protected sites arise as a result of excessive sun exposure, most likely combined with phenotypic susceptibility. The strong negative association with nevi also suggests that there are constitutional factors that underlie the propensity for BCCs to arise on these body sites.